Bayanyyahi-yi Sazmani Paykar dar Rahi Azadi-yi Tabaqahi-yi Kargar dar barahi-yi taghir va tahavvulati akhir (Fidrasiyuni Danishjuyan va Muhassilini Irani dar Faransah)
Declaration of the Organisation of Combat Organisation for Working Class Freedom on the recent changes and developments.